Effects of cold and warm thermopeaking on drift and stranding of juvenile European grayling (Thymallus thymallus). (30th November 2022) - Auer, Stefan; Hayes, Daniel S.; Führer, Simon; Zeiringer, Bernhard; Schmutz, Stefan
Abstract: Intermittent water releases from hydropower plants, called hydropeaking, negatively affect river biota. The impacts mainly depend on hydrological alterations, but changes in physical habitat conditions are suspected to be co‐responsible. For example, hydropeaking accompanied by a sudden change of water temperature in the downstream river—called thermopeaking—is also presumed to impair aquatic ecosystems. Still, knowledge about these thermopeaking impacts on aquatic species and life‐stages is limited. We performed flume experiments under semi‐natural conditions to fill this knowledge gap, simulating single hydropeaking events with a change in water temperature. As response parameters, we quantified the drift and stranding of early life‐stages of European grayling ( Thymallus thymallus L.), a key fish species of Alpine hydropeaking rivers. Hydropeaking events with a decrease in water temperature ("cold thermopeaking") led to significantly higher downstream drift (mean = 51%) than events with increasing water temperature ("warm thermopeaking", mean = 27%). Moreover, during cold thermopeaking, a comparably high fish drift was recorded up to 45 min after the start of peak flows. In contrast, drift rates quickly decreased after 15 min during warm thermopeaking. Remarkably, the spatial distribution of downstream drift along gravel bars during cold thermopeaking showed the opposite pattern compared to those triggered by warm thermopeaking events indicating different behavioral responses. Furthermore, the stranding rates of the cold thermopeaking trials were twice as high (mean = 31%) as those of the warm thermopeaking experiments (mean = 14%). The outcomes present vital information for improving mitigation measures and adapting environmental guidelines.